The Role of the National Board of Zakat in Improving the Community's Economy - Tartila, Muzayyana; Asmuni (ITQAN: Journal of Islamic Economics, Management, and Finance, 2023)
Public welfare is one aspect that must be considered by every country with various policies, but it is still not able to be implemented properly and effectively. The emergence of zakat institutions such as BAZNAS to optimize zakat funds so that they can minimize poverty and can improve the economy in society. In this case, Islam has obligated Muslims to pay zakat to achieve prosperity. The purpose of this study is to discuss the role of Zakat in improving the community's economy. This research method uses descriptive qualitative based on previous literature. The results of this study are that the role of the National Amil Zakat Agency (BAZNAS) has been carried out optimally from the collection process to distribution to the community by looking at the results from the past few years, but it is still not optimal.